2012
DOI: 10.1088/0953-8984/24/15/155303
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced dielectric constant resolution of thin insulating films by electrostatic force microscopy

Abstract: Esta es la versión de autor del artículo publicado en: This is an author produced version of a paper published in: Abstract: Electrostatic Force Microscopy has been shown to be a useful tool to determine the dielectric constant of insulating films of nanometer thicknesses that play a key role in many electrical, optical and biological phenomena. Previous approaches make use of simple analytical formulae to analyse the experimental data for thin insulating films deposited directly on a metallic substrate. Here … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Both the metallic and Air/vacuum limits correspond to a tip over a metallic sample with different tip-sample distances (D and D+h respectively). The behaviour of the force is well known for metallic samples 21 . Taken into account these previous results and the boundary conditions of a dielectric plate, a simple expression can be deduced for the electrostatic force:…”
Section: Theoretical Simulationsmentioning
confidence: 98%
“…Both the metallic and Air/vacuum limits correspond to a tip over a metallic sample with different tip-sample distances (D and D+h respectively). The behaviour of the force is well known for metallic samples 21 . Taken into account these previous results and the boundary conditions of a dielectric plate, a simple expression can be deduced for the electrostatic force:…”
Section: Theoretical Simulationsmentioning
confidence: 98%
“…[9] In the case of thin films, it has been also shown that the substrate thickness and dielectric constant are key parameters for a quantitative characterization. [10] Some effects like the detection of effective ultrahigh dielectric constants due, for example, to the presence of certain conductivity in the thin film can be also present. [11] In the EFM setup proposed in this article, there are at least three layers that could modify the magnitude and behaviour of the electrostatic force.…”
Section: mentioning
confidence: 99%
“…The details of this method, including a three layers thin film sample have been described elsewhere 10 and only a brief description is given here. Basically, the GICM can be understood by a method that includes the sample and tip shape in two steps.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…These technical improvements have been especially relevant in the characterization of thin films [7][8][9][10]. Most of the previous work has been focused on perfectly insulating dielectrics [11], but the possible effect of a small conductivity on the EFM signal has not been addressed before (i.e., previously, every layer included in the sample was only characterized by the thickness and dielectric constant). The conductivity, even with small values, is very important in the characterization of thin films in air ambient conditions where water and molecular adsorption and water condensation [12][13][14] can be detected as a finite surface conductivity due to the ions added on the otherwise insulating sample.…”
Section: Introductionmentioning
confidence: 99%